2016
DOI: 10.1056/nejmoa1513248
|View full text |Cite
|
Sign up to set email alerts
|

Ozanimod Induction and Maintenance Treatment for Ulcerative Colitis

Abstract: In this preliminary trial, ozanimod at a daily dose of 1 mg resulted in a slightly higher rate of clinical remission of ulcerative colitis than placebo. The trial was not large enough or of sufficiently long duration to establish clinical efficacy or assess safety. (Funded by Receptos; TOUCHSTONE ClinicalTrials.gov number, NCT01647516.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
298
1
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 400 publications
(322 citation statements)
references
References 20 publications
4
298
1
19
Order By: Relevance
“…For instance, ozanimod is an oral agonist of S1PR subtypes 1 and 5 that induces peripheral lymphocyte sequestration. A phase II trial indicated that ozanimod (daily dose of 1 mg) results in a slightly higher clinical remission rate in ulcerative colitis than placebo, suggesting that such drugs might be therapeutically effective in human ulcerative coli tis 73 . However, further prospective studies are needed to determine efficacy and safety of ozanimod treatment in ulcerative colitis.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…For instance, ozanimod is an oral agonist of S1PR subtypes 1 and 5 that induces peripheral lymphocyte sequestration. A phase II trial indicated that ozanimod (daily dose of 1 mg) results in a slightly higher clinical remission rate in ulcerative colitis than placebo, suggesting that such drugs might be therapeutically effective in human ulcerative coli tis 73 . However, further prospective studies are needed to determine efficacy and safety of ozanimod treatment in ulcerative colitis.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Ozanimod was studied in a phase 2 randomized controlled trial in patients with active ulcerative colitis [35] . Adults with moderate to severe UC defined by a Mayo score of 6-12 with endoscopic subscore ≥ 2 were enrolled.…”
Section: Ozanimodmentioning
confidence: 99%
“…Subjects were randomized to receive placebo 0.5 or 1 mg daily by mouth. The primary outcome was clinical remission (Mayo score ≤ 2 and no score greater than 1) at week 8, and was achieved by 13.8, 16.4 and 6.2% with ozanimod 0.5, 1 mg and placebo, respectively (p = 0.048 for ozanimod 1 mg vs. placebo) [35] . Secondary analysis included clinical response (decrease in Mayo score by ≥ 3 from baseline and decrease in rectal bleeding score by ≥ 1 or rectal bleeding score ≤ 1), seen in placebo (36.9%), 0.5 mg (53.8%) and 1.0 mg (58.2%, p = 0.01 for comparison to placebo) [35] .…”
Section: Ozanimodmentioning
confidence: 99%
See 2 more Smart Citations